A Cemented Cup with Acetabular Impaction Bone Grafting is More Cost-Effective than an Uncemented Cup in Patients under 50 Years. Issue 1 (January 2016) - Busch, Vincent J.J.F.; Verschueren, Joost; Adang, Eddy M.; Lie, Stein A.; Havelin, Leif I.; Schreurs, Berend W.
Purpose: Acetabular deficiencies in young patients can be restored in several ways during total hip arthroplasty. Currently, cementless cups are most frequently used. Impaction bone grafting of acetabular defects is a more biological approach, but is it cost-effective in young patients on the long term? Methods: We designed a decision model for a cost-utility analysis of a cemented cup with acetabular impaction bone grafting versus an uncemented cup, in terms of cost per quality-adjusted life year (QALY) for the young adult with acetabular bone deficiency, in need for a primary total hip arthroplasty. Outcome probabilities and effectiveness were derived from the Radboud University Nijmegen Medical Centre and the Norwegian Hip Register. Multiple sensitivity analyses were used to assess the contribution of the included variables in the model's outcome. Results: Cemented cups with impaction bone grafting were more cost-effective compared to the uncemented option in terms of costs per QALY. A scenario suggesting equal primary survival rates of both cemented and uncemented cups still showed an effect gain of the cemented cup with impaction bone grafting, but at higher costs. Conclusions: Based on this model, the first choice of treatment of the acetabular bone deficient osteoarthritic hip in a young patient is reconstruction with impaction bone grafting and a cemented cup.